(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article examines the influence on the formation of Outlook of the poet’s tragic life and creative path, originality and uniqueness of the poetics, of the uniqueness of the world view and Outlook poet, the innovation Paul Celan in the field of poetic language.